Comparable cumulative incidence of late periprosthetic femoral fracture and aseptic stem loosening in uncemented total hip arthroplasty: a concise follow-up report at a minimum of 20 years - Innmann, Moritz Maximilian; Streit, Marcus R.; Bruckner, Thomas; Merle, Christian; Gotterbarm, Tobias (The journal of arthroplasty, 2018)
Background: There is a lack of long-term studies into the third decade reporting on the incidence of periprosthetic femoral fracture (PPFF) and aseptic stem loosening (ASL) after cementless total hip arthroplasty (THA). The aim of the present retrospective, longitudinal cohort study was to compare the cumulative incidence of PPFF and ASL in a consecutive cohort of 326 patients with 354 primary uncemented THAs after 20-25 years and to identify risk factors being associated with PPFFs. Methods: Postoperative femoral fractures were investigated for timing, mechanism of injury, Vancouver classification, and subsequent treatment. The cumulative incidence of PPFF and ASL was estimated using Kaplan-Meier survival analysis. Risk factors for PPFFs were analyzed using a Cox proportional hazards regression model. Results: One hundred sixty-three patients (180 hips) were available for follow-up at a mean of 22 years. Twenty-one fractures occurred during the follow-up period. The cumulative incidence of PPFF was 1.6% at 10 years, 4.5% at 17 years, and 9.4% at 22 years after surgery. The cumulative incidence of PPFF and ASL after 22 years was comparable (9.4% [95% confidence interval, 5.9%-14.7%] and 6.9% [95% confidence interval, 4.5%-10.5%]). Gender, age at surgery, diagnosis, cup revision, and canal fill index of the stem in the proximal femur were no risk factors for the occurrence of a PPFF. Conclusion: The cumulative incidence of PPFF after primary uncemented THA further increased in the second decade and reached the incidence of ASL in the third decade, while no risk factors for the occurrence of a PPFF could be identified.
Online 16 November 2017
Gesehen am 20.11.2018